Perguruan Tinggi Berbasis Pesantren: Menggagas Interkoneksi Agama dan Sains - Munif, Muhammad; Baharun, Hasan (LP2M IAIN kUDUS, 2018)
This research presents about college strategy based on pesantren in realizing the interconnection of religion and science in Sekolah Tinggi Tekhnologi dan Sekolah Tinggi Ilmu Kesehatan Nurul Jadid Paiton Probolinggo. Interconnection of religion and science as a concept that offers for the relationship between discipline of science of religion and general science. The estuary of the interconnection of religion and science is to unite and make a connection between religious education and science. This research uses qualitative approach of case study type. The results show that; 1) The interconnection strategy of religion and science conducted by Sekolah Tinggi Tekhnologi (STT) Nurul Jadid and Sekolah Tinggi Ilmu Kesehatan (STIKes) Nurul Jadid Paiton Probolinggo include; internal and external environment analysis, vision and mission determination, mindset change, curriculum development with integration pattern, strengthening of human resource quality, formation of religious culture. 2) the impact of the interconnection of religion and science is; the inclusive attitude in understanding the development of science and religion, has a global perspective, the achievement of the vision and mission of the institution as the leader of the vision and mission of pesantren.